A study on the awareness of cosmetic products among Diploma Students UiTM Puncak Alam / Nur A’fina Mohamad Sopee - Mohamad Sopee, Nur A’fina (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
In this modern era, we can clearly see that cosmetic products are everywhere and widely used by the consumers especially for women which are naturally love beauty but these days men are also fall into this trap which is they are also interested in this kind of products. But the question is, does everyone aware about the cosmetic products that they have used give good or bad result to them? Because most of these people just want to beautiful and attractive without knowing the impacts that might happen to their face, hair, body and even the organs in our body because it affects all of it. So, this study has the objectives to know how much the consumers and other people know about the cosmetic products. First of all, one of the objectives is to know the understanding of cosmetic products among the people. It consists the definition of the cosmetics itself, the example of types which what is more part in cosmetic products like skin care products are part of it and it discuss about several ingredients in the cosmetic products which are good and hazardous ingredients in it. Moreover, this study aims to know the level of the awareness about cosmetic products among these people which is including whether they read the ingredients of the products, choose the most popular products and about organic and chemical cosmetic products. It is also consist of the impacts that might happen to the consumers which is talk about the selfconfidence level, the testimony and spending money on the cosmetic products. In order to know all of that, the questionnaires have been given to the several consumers and people randomly. So, it can be concluded that the objectives of this study have been achieved successfully based on the researches that have done.